Alcohol Drinking Patterns and Suicidal Risks of Clients Receiving Services at Mental Health and Psychiatric Clinics - Srinor, Pattarin; Skulphan , Sombat; Sethaboupph, Hunsaa (Nursing Journal CMU, 2022)
Suicide is a major mental health and psychiatric problem with incidents across all regions of the world including Thailand. This problem causes a massive loss of human resources and affects the people surrounding the person with the problem. Drinking alcohol is one factor related to suicidal risk. The purpose of this descriptive correlational research was to study the relationship between alcohol drinking patterns and suicidal risk of clients receiving services at mental health and psychiatric clinics. Participants included 378 clients between 25-59 years old who received services at mental health and psychiatric clinics in community hospitals located in Northeast Thailand. The research instruments consisted of personal questionnaires, the Alcohol Use Identification Test (AUDIT), and the Mini Inter- national Neuropsychiatric Structured Interview [M.I.N.I.] for suicidality. The data were analyzed by descriptive statistics and Spearman’s rank correlation coefficient. The results revealed that 1. Most of the participants (69.3%) had alcohol drinking patterns, which could be divided into four patterns: low-risk drinking (57.3%), hazardous drinking (21.8%), harmful drinking (6.5%), and dependence drinking (14.5%). 2. Some participants (33.1%) experienced suicidal risk, which could be divided into the following levels: low risk (80%), moderate risk (13.6%), and high risk (6.4%). 3. There was no statistically significant relationship between suicidal risk and any of the four alcohol drinking patterns. Mental health staff at community hospitals should screen clients for alcohol drinking problems and suicidal risk in order to develop problem prevention guidelines for clients in the healthcare system.